SHOPEEPAY MOBILE PAYMENT ADOPTION ANALYSIS USING THE UTAUT MODEL APPROACH (CASE STUDY AT AMIKOM UNIVERSITY YOGYAKARTA) - Widiyanti Kurnianingsih (Program Studi S1 Sistem Informasi Fakultas Komputer dan Teknik Universitas Alma Ata, 2022)
Along with the development of time, fintech companies issued mobile payment products such as QR Code, NFC, and OTP codes. The use of payment facilities that are currently rampant causes users to choose according to their wishes, based on the description, the purpose of this study is to analyze the use of ShopeePay mobile payments using the UTAUT approach. The variables analyzed are Perceived Risk, Perceived Trust, Perceived Cost, Self-efficacy, Effort expectancy, performance expectancy, and Social Influence on mobile payment adoption at Shopeepay. The research method used in this case is a descriptive method, using statistical data processing tools. Data collection was carried out at Amikom University Yogyakarta using the sampling method. The results showed that the factors perceived risk (perceived risk), self-efficacy (self-efficacy), and effort expectancy (business expectations) had a positive and significant effect on interest in mobile payment adoption in Indonesia. . Furthermore, the factors of perceived trust (perceived trust), performance expectancy (performance expectations), and social influence (social influence) do not have a positive effect on interest in mobile payment adoption in Indonesia.